Working with and learning from Country: decentring human author-ity. (April 2015) - Country, Bawaka; Wright, Sarah; Suchet-Pearson, Sandie; Lloyd, Kate; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr-Stubbs, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil
In this paper, we invite you night fishing for wäkun at Bawaka, an Indigenous homeland in North East Arnhem Land, Australia. As we hunt wäkun, we discuss our work as an Indigenous and non-Indigenous, human and more-than-human research collective trying to attend deeply to the messages we send and receive from, with and as a part of Country. The wäkun, and all the animals, plants, winds, processes, things, dreams and people that emerge together in nourishing, co-constitutive ways to create Bawaka Country, are the author-ity of our research. Our reflection is both methodological and ontological as we aim to attend deeply to Country and deliberate on what a Yolŋu ontology of co-becoming, that sees everything as knowledgeable, vital and interconnected, might mean for the way academics do research. We discuss a methodology of attending underpinned by a relational ethics of care. Here, care stems from an awareness of our essential co-constitution as we care for, and are cared for by, the myriad human and more-than-human becomings that emerge together to create Bawaka. We propose that practising relational research requires researchers to open themselves up to the reality of their connections with the world, and consider what it means to live as part of the world, rather than distinct from it. We end with a call to go beyond 'human' geography to embrace a more-than-human geography, a geography of co-becoming.